Faktor-Faktor yang Berhubungan dengan Kejadian Needle Stick Injury pada Perawat Di Rumah Sakit: Systematic Literature Review - Fadilah, Sylva Qamara Nur; Susilawati (RADINKA JOURNAL OF HEALTH SCIENCE, 2024)
Hospitals have many potential occupational safety and health (K3) hazards for their nurses. One example is nosocomial infections caused by puncture and/or incision wounds (CTS). Needle Stick Injury (NSI) occurs when hypodermic needles, such as hypodermic syringes, blood draw needles, intravenous syringes, and connecting needles from intravenous administration systems, accidentally puncture the skin. The research method used is a systematic literature review of previous research results. The research results show that the incidence of needle stick injury (NSI) is influenced by several factors. Associated factors include age, minimal experience, participation in training, and acceptance of HB vaccination. Controlling the incidence of needle stick injuries can be done by providing regular training so that nurses can continue to improve their competency and reduce the risk of accidents.